Development of Oncolytic Vectors Based on Human Adenovirus Type 6 for Cancer Treatment - Ivan D. Osipov; Valeriia A. Vasikhovskaia; Daria S. Zabelina; Sergei S. Kutseikin; Antonina A. Grazhdantseva; Galina V. Kochneva; Julia Davydova; Sergey V. Netesov; Margarita V. Romanenko (Viruses, 2023)
Human Adenovirus type 6 (HAdV-C6) is a promising candidate for the development of oncolytic vectors as it has low seroprevalence and the intrinsic ability to evade tissue macrophages. However, its further development as a therapeutic agent is hampered by the lack of convenient cloning methods. We have developed a novel technology when a shuttle plasmid carrying the distal genome parts with modified E1A and E3 regions is recombined in vitro with the truncated HAdV-C6 genome. Using this approach, we have constructed a novel Ad6-hT-GM vector controlled by the hTERT promoter and expressing granulocyte-macrophage colony-stimulating factor (GM-CSF) instead of 6.7K and gp19K E3 proteins. We have demonstrated that control by the hTERT promoter may result in delayed viral replication, which nevertheless does not significantly change the cytotoxic ability of recombinant viruses. The insertion of the transgene by displacing the E3-6.7K/gp19K region does not drastically change the expression patterns of E3 genes; however, mild changes in expression from major late promoter were observed. Finally, we have demonstrated that the treatment of human breast cancer xenografts in murine models with Ad6-hT-GM significantly decreased the tumor volume and improved survival time compared to mock-treated mice.